Inheriting jobs in Damascus during the Ayyubid and Mamluk periods: Financial management jobs as a model - Awad, Riad Salim (Al-Adab Journal, 2023)
During the rule of the Ayyubid and Mamluk states, a number of functions of financial management emerged in Damascus, such as the calculation – alhusba - and agency of the treasury house - wikalat bayt al-mal- , in addition to the function of the overseer – al-nazar-, It was distinguished by a feature that was demonstrated by the historical sources that spoke about the history of the Islamic administrative system, namely the feature of inheriting these functions among some of the scholars of the famous families, the prevalence of this phenomenon reflected a set of historical facts about the features of the administrative system in Damascus, including that the family has an important role in supporting the administrative life, and that the ruling authority agreed to the continuation of this phenomenon - inheriting jobs - among those scientific families because they are confident that the correct tool for evaluating the administrative apparatus in the country He is the scholar who is the son of these ancient families, in other words, the long history that the family owned was a reason for the authority to choose its scholars to take over the functions of financial management at the time.